2011
DOI: 10.1109/jstsp.2010.2100365
|View full text |Cite
|
Sign up to set email alerts
|

Displacement Estimation by Maximum-Likelihood Texture Tracking

Abstract: Abstract-This paper presents a novel method to estimate displacement by maximum-likelihood (ML) texture tracking. The observed polarimetric synthetic aperture radar (PolSAR) data-set is composed by two terms: the scalar texture parameter and the speckle component. Based on the Spherically Invariant Random Vectors (SIRV) theory, the ML estimator of the texture is computed. A generalization of the ML texture tracking based on the Fisher probability density function (pdf) modeling is introduced. For random variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
(58 reference statements)
0
9
0
2
Order By: Relevance
“…For the detection of grazing/cutting event more precisely the ground truth data will be collected during the SAR acquisition days. In recent studies authors [43], [44] showed the application of Fisher probability distribution for SAR texture modeling and texture tracking for displacement estimation. In future works, the Fisher probability distributions will be also addressed to calculate the theoretical mean value of backscattering coefficients for different land cover and habitat types.…”
Section: Discussionmentioning
confidence: 99%
“…For the detection of grazing/cutting event more precisely the ground truth data will be collected during the SAR acquisition days. In recent studies authors [43], [44] showed the application of Fisher probability distribution for SAR texture modeling and texture tracking for displacement estimation. In future works, the Fisher probability distributions will be also addressed to calculate the theoretical mean value of backscattering coefficients for different land cover and habitat types.…”
Section: Discussionmentioning
confidence: 99%
“…If no redundant observations are available, then the stationarity of the flow direction can be used to derive confidence measures reflecting the temporal directional coherence of the 2D velocity vectors. For example, in [22] or [8], the assumption of a displacement flow in the direction of the maximum downhill slope was considered to study glaciers. This implies that, for a given location, the glacier displacement direction at different dates must be similar.…”
Section: Confidence Measure Computationmentioning
confidence: 99%
“…The K most expected and the K most unexpected reliable GFS-patterns are finally retained, with K a user defined parameter. 8…”
Section: Pattern Selection and Rankingmentioning
confidence: 99%
“…However, these installations are usually limited by the difficult access to many glacier areas and the expensive maintenance in glacier areas. In the recent years, the remote sensing data acquired by air-borne or space-borne sensors are largely used in complement to in-situ measurements, which allows regular dense measurements of glacier displacement to be performed over large area [2,3,4,5]. The latter is crucial for significant change detection of some physical parameters, as well as for glacier flow model constrain.…”
Section: Introductionmentioning
confidence: 99%